Lean manufacturing : implementation, strategies that work: a roadmap to quick and lasting success - Davis, John W. , 1938- (Industrial Press, 2009)
Offers an approach to implementing Lean manufacturing, pointing out the stumbling blocks and pitfalls to avoid. This title helps American manufacturing effectively go about the task of making Lean a viable process. It provides readers with a path to inserting Lean in a manufacturing operation and a step by step approach to getting there.